Strategi Hubungan Masyarakat (Humas) dalam Memperkuat Citra dan Positioning Sekolah Menengah Kejuruan Negeri (SMKN) di Kawasan Ibu Kota Nusantara - Anita Dwi Basuki; Muh. Amir Masruhim (Universitas Negeri Malang, 2025)
Abstract: Formation of a positive image of SMK is an effort to increase the level of competition amidst the progress of the development of the Capital Region of Nusantara. The purpose of this study is to describe the planning, organization, implementation, and evaluation of Public Relations (PR) strategies in strengthening the image and positioning of State Vocational High Schools in the Capital Region of the Archipelago. This study uses a qualitative approach with a case study method in three State Vocational High Schools in Penajam Paser Utara Regency, the Capital Region of the Archipelago, data collection techniques in the form of interviews, observations and documentation, with data validity checks through triangulation of techniques and sources. The results of the study indicate that public relations strategy planning is carried out through an early school year meeting with a focus on strengthening external relations, school branding, and increasing industrial cooperation. The organization of the strategy is adjusted to the conditions and resources of each school. The implementation of the strategy involves the use of social media, as well as active collaboration with the business world and industry. Program evaluations are carried out periodically to measure the effectiveness in building the school's image. This study confirms that public relations have a strategic role in shaping public perception and increasing the competitiveness of vocational schools, especially amidst the rapid development of the Public Relations; Image; School Positioning; Capital Region of the Archipelago. Keywords: Public Relations, Image, School Positioning, Capital Region of Nusantara Abstrak: Pembentukan citra positif SMK adalah sebuah upaya terhadap meningkatnya tingkat persaingan di tengah kemajuan pembangunan Ibu Kota Nusantara (IKN). Tujuan penelitian ini adalah untuk mendeskripsikan perencanaan, pengorganisasian, pelaksanaan, dan evaluasi strategi Hubungan Masyarakat (Humas) dalam memperkuat citra dan positioning Sekolah Menengah Kejuruan Negeri (SMKN) di Kawasan Ibu Kota Nusantara. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus di tiga SMK Negeri di kabupaten Penajam Paser Utara kawasan Ibu Kota Nusantara, teknik pengumpulan data berupa wawancara, observasi dan dokumentasi, dengan pemeriksaan keabsahan data melalui triangulasi teknik dan sumber. Hasil penelitian menunjukkan bahwa perencanaan strategi humas dilakukan melalui rapat awal tahun ajaran dengan fokus pada penguatan hubungan eksternal, branding sekolah, dan peningkatan kerja sama industri. Pengorganisasian strategi menyesuaikan dengan kondisi dan sumber daya masing-masing sekolah. Pelaksanaan strategi melibatkan penggunaan media sosial, serta kolaborasi aktif dengan dunia usaha dan industri. Evaluasi program dilakukan secara berkala untuk mengukur efektivitas dalam membangun citra sekolah. Penelitian ini menegaskan bahwa humas memiliki peran strategis dalam membentuk persepsi publik dan meningkatkan daya saing SMK, khususnya di tengah perkembangan pesat Ibu Kota Nusantara. Kata kunci: Hubungan Masyarakat, Citra, Positioning Sekolah, Ibu Kota Nusantara